PENGARUH UKURAN PERUSAHAAN, RISIKO PERUSAHAAN, INTENSITAS MODAL DAN STRUKTUR KEPEMILIKAN TERHADAP PENERAPAN KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Periode 2019 -2021) - Jesica, Jesica; Manik, Ester Tiorida Br; Rasyikah, Filza; Rahmi, Namira Ufrida; Lubis, Putri Kemala Dewi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research investigates how accounting conservatism in BEI manufacturing companies from 2019 to 2021 is impacted by size, risk, capital intensity and ownership structure. Over 3 years, 78 companies were selected using the purposive sampling method. This 2019-2021 research was carried out using SPSS, and multiple linear regression, descriptive tests, classical assumptions, multiple linear regression, F test, T test, and coefficient of determination. This research also found that company size, risk, capital intensity and ownership structure have an impact on accounting conservatism in manufacturing companies on the IDX.